2022
DOI: 10.1038/s41385-022-00517-8
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with a mucosal viral pandemic: lessons from COVID-19 vaccines

Abstract: The development and deployment of vaccines against COVID-19 demonstrated major successes in providing immunity and preventing severe disease and death. Yet SARS-CoV-2 evolves and vaccine-induced protection wanes, meaning progress in vaccination strategies is of upmost importance. New vaccines directed at emerging viral strains are being developed while vaccination schemes with booster doses and combinations of different platform-based vaccines are being tested in trials and real-world settings. Despite these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 105 publications
0
55
0
Order By: Relevance
“…However, inducing superior anti-SARS-CoV-2 mucosal immunity using innovative vaccines remains an important goal in stopping viral transmission. Several preclinical studies show that intranasal or orally administered adenoviral-based vaccines can protect against transmission and reduce disease severity [ 17 ], inducing mucosal specific IgA and tissue-resident memory cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, inducing superior anti-SARS-CoV-2 mucosal immunity using innovative vaccines remains an important goal in stopping viral transmission. Several preclinical studies show that intranasal or orally administered adenoviral-based vaccines can protect against transmission and reduce disease severity [ 17 ], inducing mucosal specific IgA and tissue-resident memory cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these it is notable that intranasal vaccination has been successfully developed against influenza virus, thereby affording precedent for this approach against SARS-CoV-2. Numerous groups have indeed taken up the challenge and demonstrated that intranasal immunization with a variety of vaccine constructs can induce antibodies with virus-neutralizing capability in secretions as well as serum, and even protective immunity against challenge, in animals such as mice ( 86 , 87 ), hamsters ( 88 , 89 ), and monkeys ( 90 , 91 , reviewed in 92 , 93 ). However, few of these efforts have advanced into clinical trials beyond phase I.…”
Section: Are Mucosal Vaccines the Answer? Of Mice And Humansmentioning
confidence: 99%
“…The prevention of infection implies a mechanism that is either a rapid antibody and T cell response to a pre-symptomatic viral load, or the prevention of cellular infection completely by opsonisation and neutralisation. The pure prevention mechanism is consistent with mucosal immunity [25][26][27] and allows decoupling of the antibody levels from T and B cell memory responses that require infected cells to trigger the adaptive response. Further, the total T cell density in the mucosa is ~650 mm -2 , varying over a factor of five 14 , and would increase response once epithelial cells have been infected by inducing recruitment of further T cells from the blood.…”
Section: Resultsmentioning
confidence: 69%